A novel optical biosensor for in situ and small-scale monitoring of bacterial transport in saturated columns. (1st July 2021) - Tao, Wei; Song, Yantao; Singhal, Naresh; McGoverin, Cushla; Vanholsbeeck, Frédérique; Swift, Simon
Abstract: In situ monitoring techniques can provide new insight into bacterial transport after inoculating exogenous bacteria into contaminated soils for bioremediation. A real-time and non-destructive optical sensor (the optrode) was employed to monitor in situ transport of two fluorescently labelled bacteria – Green Fluorescent Protein (Gfp)-labelled, hydrophilic Pseudomonas putida and Tomato Fluorescent Protein (td)-labelled, hydrophobic Rhodococcus erythropolis, in a saturated sand column with and without rhamnolipid surfactant. In situ measurements were made at three sampling ports in the column with the optrode in two sets of column experiments. In Experiment 1, liquid samples were extracted for ex situ analyses (plate counts and fluorescence), while in Experiment 2 no liquid samples were extracted. Extracting liquid samples for ex situ analyses in Experiment 1 disturbed in situ measurements; in situ measured bacterial concentrations were lower, or a significant lag in breakthrough occurred relative to ex situ measurements. In Experiment 2, the optrode worked well in monitoring bacterial transport, which gave consistent transport parameters at each sampling port. Moreover, the optrode enabled the impact of bacterial hydrophobicity and rhamnolipid surfactant on bacterial transport to be observed. Specifically, hydrophilic P. putida was transported faster through the column than hydrophobic R. erythropolis ; we infer from this result that fewer P. putida cells adsorb to sand particles than do R. erythropolis cells. The rhamnolipid surfactant enhanced the transport of both hydrophilic and hydrophobic bacteria. These two observations are consistent with Lifshitz–van der Waals forces and acid-base interactions between bacteria and sand. Highlights: We present a device, the optrode, for monitoring bacteria in situ in sand columns. Concurrent ex situ sampling affects optrode in situ measurements. Transport of bacteria can be monitored without sample extraction. The hydrophobicity of bacteria affects their transport. Rhamnolipid surfactant improves transport of hydrophilic and hydrophobic bacteria.